Contribution to the knowledge of the seaweeds of Alboran Island (Western Mediterranean) - Conde, Francisco; Flores-Moya, Antonio (Acta Botanica Malacitana, 2000)
Contribution to the knowledge of the seaweeds of Alboran Island (Western Mediterranean)